The BiTE (bispecific T‐cell engager) platform: Development and future potential of a targeted immuno‐oncology therapy across tumor types. Issue 14 (13th May 2020) - Einsele, Hermann; Borghaei, Hossein; Orlowski, Robert Z.; Subklewe, Marion; Roboz, Gail J.; Zugmaier, Gerhard; Kufer, Peter; Iskander, Karim; Kantarjian, Hagop M.
Abstract : Immuno‐oncology therapies engage the immune system to treat cancer. BiTE (bispecific T‐cell engager) technology is a targeted immuno‐oncology platform that connects patients' own T cells to malignant cells. The modular nature of BiTE technology facilitates the generation of molecules against tumor‐specific antigens, allowing off‐the‐shelf immuno‐oncotherapy. Blinatumomab was the first approved canonical BiTE molecule and targets CD19 surface antigens on B cells, making blinatumomab largely independent of genetic alterations or intracellular escape mechanisms. Additional BiTE molecules in development target other hematologic malignancies (eg, multiple myeloma, acute myeloid leukemia, and B‐cell non‐Hodgkin lymphoma) and solid tumors (eg, prostate cancer, glioblastoma, gastric cancer, and small‐cell lung cancer). BiTE molecules with an extended half‐life relative to the canonical BiTE molecules are also being developed. Advances in immuno‐oncology made with BiTE technology could substantially improve the treatment of hematologic and solid tumors and offer enhanced activity in combination with other treatments. Abstract : This review provides an overview of immuno‐oncology therapies and those in development. It specifically focuses on bispecific T‐cell engager (BiTE) technology, its mechanism of action, types of cancer in which it has had success, half‐life‐extended BiTE molecules, and their potential as an off‐the‐shelf, targeted immunotherapy.